Associations of childhood hearing loss and adverse childhood experiences in deaf adults. - Wyatte C Hall; Timothy D V Dye; Shazia Siddiqi (PLoS ONE)
Childhood trauma and adverse childhood experiences have a strong relationship with health disparities across the lifespan. Despite experiencing approximately doubled rates of trauma, Adverse Childhood Experiences (ACEs) are poorly characterized in deaf populations. We sought to characterize deaf-specific demographic factors and their association with multiple experiences of ACEs before the age of 18 years old. An analytical cross-sectional approach was used to ascertain associations of deaf-specific demographic factors and experiences with ACEs. The complete dataset included 520 participants for a total response rate of 56%. After adjusting for confounding effects, less severe hearing loss of 16-55 dB (2+ OR: 5.2, 4+ OR: 4.7), having a cochlear implant (2+ OR: 2.1, 4+ OR: 2.6), and not attending at least one school with signing access (2+ OR: 2.4, 4+ OR: 3.7) were significantly and independently associated with reported experiences of multiple ACEs. We conclude that factors associated with childhood hearing loss and language experiences increase risk of experiencing ACEs. Given the strong relationship between ACEs and poor social outcomes, early intervention clinical practice and health policies should consider interventions to support healthy home environments for deaf children.